Ultralow Roll‐Off Quantum Dot Light‐Emitting Diodes Using Engineered Carrier Injection Layer - Liao, Zebing; Mallem, Kumar; Prodanov, Maksym F.; Kang, Chengbin; Gao, Yiyang; Song, Jianxin; Vashchenko, Valerii V.; Srivastava, Abhishek K. (Advanced materials (Weinheim), 2023)
Quantum dot (QD) light‐emitting diodes (QLEDs) have attracted extensive attention due to their high color purity, solution‐processability, and high brightness. Due to extensive efforts, the external quantum efficiency (EQE) of QLEDs has approached the theoretical limit. However, because of the efficiency roll‐off, the high EQE can only be achieved at relatively low luminance, hindering their application in high‐brightness devices such as near‐to‐eye displays and lighting applications. Here, this article reports an ultralow roll‐off QLED that is achieved by simultaneously blocking electron leakage and enhancing the hole injection, thereby shifting the recombination zone back to the emitting QDs layer. These devices maintain EQE over 20.6% up to 1000 mA cm−2 current density, dropping only by ≈5% from the peak EQE of 21.6%, which is the highest value ever reported for the bottom‐emitting red QLEDs. Furthermore, the maximum luminance of the optimal device reaches 320 000 cd m−2, 2.7 times higher than the control device (Lmax: 128 000 cd m−2). A passive matrix (PM) QLED display panel with high brightness based on the optimized device structure is also demonstrated. The proposed approach advances the potential of QLEDs to operate efficiently in high‐brightness scenarios. The quantum dot light‐emitting diodes (QLEDs) can only achieve high external quantum efficiency (EQE) at relatively low current density due to the efficiency roll‐off effect. Here, this article reports an ultralow roll‐off QLED, the EQE maintained over 20.6% up to 1000 mA cm−2, dropping only by ≈5% from the peak EQE of 21.6%.